Co-occurrence patterns and assembly processes of microeukaryotic communities in a semi-enclosed aquaculture bay. (1st October 2021) - Ma, Yifan; Pan, Yongbo; Liu, Qianqian; Huang, Lingfeng; Zhang, Wenjing
Abstract: Little was known about the biogeographical patterns, interaction and assembly processes of microeukaryotic communities in semi-enclosed aquaculture bays. Here, we examined microeukaryotic communities in 53 water samples from Sansha Bay (a typical semi-enclosed aquaculture bay), China. We found 9, 282 operational taxonomic units (OTUs, 97% sequence identity), including 25 abundant OTUs and 8, 919 rare OTUs. Ciliophora and Dinoflagellata were the most diverse and abundant lineages. (i) Although the degree of separation was different, both abundant and rare taxa showed significant separation between the three aquaculture areas (MAC, macroalgal culture; CAC, cage culture ( Larimichthys crocea ); and MIC, mixed culture) of the bay. Significant distance-decay relationships (DDRs) were found for both abundant and rare taxa in the bay, and the DDRs of rare taxa was stronger. Dispersal limitation was the main inducement to form this pattern. (ii) Co-occurrence network analysis revealed a complex interaction pattern dominated by cooperative relationships (84.15%). There were different ecological modules in the network, and they are closely related to different aquaculture areas. Aquaculture activities and taxonomic relatedness were important factors for the co-occurrence pattern of microeukaryotes. In addition, rare taxa enhanced the community habitat specificity and occupied most (71.3%) of the key nodes (including module hubs and connectors) in the network, suggesting that rare taxa played an important role in maintaining the stability of microeukaryotic community and co-occurrence pattern. (iii) Variation partitioning analysis (VPA) indicated that spatial factors exhibited greater influence on both abundant and rare taxa than environmental variables. More importantly, rare taxa was primarily governed by stochastic processes (NSTjac  = 67.8% ± 1.9%), while deterministic processes played a decisive role in abundant taxa assembly (NSTjac  = 21.5% ± 2.5%). Highlights: Dispersal limitation was the main inducement for distance-decay patterns of microeukaryotes in Sansha bay. Rare taxa were important for the community stability and co-occurrence pattern (dominated by cooperation). Aquaculture activities and taxonomic relatedness are the key factors in determining the module structure in the network. Environmental and spatial variables played a simultaneous role in microeukaryotic community assembly. Rare taxa were mainly governed by stochastic processes, while abundant taxa were mainly governed by deterministic processes.